PERANCANGAN SISTEM INFORMASI PELAYANAN PELANGGAN PADA CITRA LAUNDRY BOGOR - Helling, Lydia Salvina (Universitas Nusantara PGRI Kediri, 2018)
Clean clothes are very necessary human to treat themselves to stay healthy and protected from all kinds of diseases that come from viruses and bacteria that live and grow around humans. One effort to keep clothes clean is to wash regularly clothes that have been exposed to dirt coming from dust, garbage, and odor. Washing activities are activities that take a lot of time because this activity is done with great care. This encourages the business to open a laundry business, even now developing not only washing clothes but serving the laundering of various types of goods made of fine fiber materials such as cotton, wool, polyester, and others. Customer service, washing quality, and washing time become the point of consumer satisfaction assessment of laundry services offered. Consumer Service System which was originally manual and then replaced with a computerized Consumer Service System. The process of data processing was switched into a database and the use of application programs. Citra Laundry then took this opportunity by providing customer service information system. Development of customer service system using Waterfall method in the software. The description of the current system and proposed system is described in the form of data flow diagrams, Kendall and Kendall methods. Data collection is done by observation on the same type of business and conducting interviews with related parties. The results of this study resulted in a customer service information system more efficient in the storage and processing of large data and very effective in dealing with the needs of customer service quickly and systematically.